Pengembangan LKS dengan pendekatan RME terhadap kemampuan kreatif dan kolaborasi siswa - Puji Anggraeni; Aritsya Imswatama; Yanti Mulyanti (De Fermat : Jurnal Pendidikan Matematika, 2021)
The importance of creative thinking and collaboration so that every learning process must be able to develo those abilities. But students’ interest in math is so low that it’s hard to develop those abilities. One cause is lack of teaching material that can show students that math exists in their daily lives. The purpose of this research is developing and producing student workbook with Realistic Mathematic Education approach to student creative thinking and collaboration valid. Developing model that used in this research is ADDIE (Analysis, Design, Development, Implementation and Evaluation). The questionnaire tests of validity. Validity test result by validators was avowed very valid with percentage 90,1%. The result showed that student mathematic workbook with RME approach was valid and facilitating student creative thinking and collaboration.